Effect of tillage and residue management in rice-wheat system - KUMAR, PARVEEN; CHAUDHARI, S K; SINGH, AJAY; SINGH, RAKESH; MISHRA, A K; SINGH, KAILASH; SHARMA, D K (The Indian Journal of Agricultural Sciences, 2021)
The declining soil health in Indo-Gangetic plains due to intensive tillage practice and residue burning is threatening the sustainability of rice-wheat system (RWS) in this region. Zero tillage (ZT) and residue recycling (incorporation/ mulching) can improve soil health and sustainability of RWS. With this hypothesis an experiment was conducted at ICAR-Central Soil Salinity Research Institute, Karnal (Haryana) to study the effect of ZT and residue recycling in rice and wheat crops on productivity, carbon sequestration, biomass accumulation and physiological growth. The highest grain yield in rice (over varieties) was recorded in PTR+RI (4.71 t/ha) followed by PTR-WR (4.45 t/ha). However, the highest shoot biomass (14.5 t/ha) and carbon sequestration (6.5 t/ha) was recorded in PTR-WR. In wheat crop (over varieties), CTW+RI produced the highest grain yield (5.10 t/ha), shoot biomass (13.6 t/ha), carbon sequestration in above ground parts (4.25 t/ha) and chlorophyll content. Rice variety CSR 36 performed better in terms of grain yield (4.91 t/ha), shoot biomass (14.7 t/ha) and carbon sequestration (6.8 t/ha) while two wheat cultivars produced similar grain yield. So, based on our experiment it can be concluded that residue incorporation in conventional practice in both the crop i.e., conventional tilled puddle transplanted rice and conventional tilled wheat performed better than residue mulched under zero tillage condition.